Reporting guideline for interventional trials of primary and incisional ventral hernia repair. Issue 9 (21st July 2021) - Parker, S G; Halligan, S; Berrevoet, F; de Beaux, A C; East, B; Eker, H H; Jensen, K K; Jorgensen, L N; Montgomery, A; Morales-Conde, S; Miserez, M; Renard, Y; et al.
Abstract: Background: Primary and incisional ventral hernia trials collect unstandardized inconsistent data, limiting data interpretation and comparison. This study aimed to create two minimum data sets for primary and incisional ventral hernia interventional trials to standardize data collection and improve trial comparison. To support these data sets, standardized patient-reported outcome measures and trial methodology criteria were created. Methods: To construct these data sets, nominal group technique methodology was employed, involving 15 internationally recognized abdominal wall surgeons and two patient representatives. Initially a maximum data set was created from previous systematic and panellist reviews. Thereafter, three stages of voting took place: stage 1, selection of the number of variables for data set inclusion; stage 2, selection of variables to be included; and stage 3, selection of variable definitions and detection methods. A steering committee interpreted and analysed the data. Results: The maximum data set contained 245 variables. The three stages of voting commenced in October 2019 and had been completed by July 2020. The final primary ventral hernia data set included 32 variables, the incisional ventral hernia data set included 40 variables, the patient-reported outcome measures tool contained 25 questions, and 40 methodological criteria were chosen. The best known variable definitions were selected for accurate variable description. CT was selected as the optimal preoperative descriptor of hernia morphology. Standardized follow-up at 30 days, 1 year, and 5 years was selected. Conclusion: These minimum data sets, patient-reported outcome measures, and methodological criteria have allowed creation of a manual for investigators aiming to undertake primary ventral hernia or incisional ventral hernia interventional trials. Adopting these data sets will improve trial methods and comparisons. Abstract : Using the nominal group technique, minimum data sets for primary and incisional ventral hernia interventional trials were created. A set of patient-reported outcomes as well as robust trial methodology criteria were also produced. A manual has been created for investigators aiming to perform primary or incisional ventral hernia interventional trials; using this manual will improve trial methodology and data comparison.